Blue vitiligo following intralesional injection of psoralen combined with ultraviolet B radiation therapy. (1st April 2015) - Zhang, J. A.; Yu, J. B.; Lv, Y.; Thapa, P.
Summary: A 23‐year‐old Chinese man presented with a 16‐month history of white patches on his abdomen and neck. He had previously received an intralesional injection of psoralen along with narrowband psoralen ultraviolet B radiation (PUVB) therapy. Blue macules had appeared in and around the injection sites 1 week later. Dermoscopy revealed blue spots and reticular telangiectasia within the white patches. Histological examination revealed an absence of epidermal melanocytes and pigment in the basal layer, as well as deposition of melanophages between collagen bundles or surrounding blood vessels and appendages in the middle and lower parts of the dermis. A diagnosis of blue vitiligo was made. The blue colour faded gradually over time. Our case provides direct evidence to support the previous surmise that PUVB can contribute to blue vitiligo. To our knowledge, this is only the fourth reported case of blue vitiligo in the English literature.